ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MATERI PECAHAN PADA TEKS NONFIKSI TEMA 7 SUBTEMA 2 KELAS IV SDN GAYAMSARI 01 SEMARANG - Putri, Lidya Karulina; Cahyadi, Fajar; Mudzanatun, Mudzanatun (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2022)
The purpose of this study was to determine the ability to solve mathematical problems with fractions in non-fiction texts in class IV at SDN Gayamsari 01 Semarang. This research uses descriptive qualitative method. Based on the results of the research conducted, it can be concluded that the mathematical problem solving ability of fractions in the non-fiction text of fourth grade students at SDN Gayamsari 01 Semarang has been carried out well with the high category there are 6 students or 19.4%, in the medium category there are 8 students or 25.8 % percent, in the low category there are 7 students or 22.6% and in the very low category there are 10 students or 32.2%. Through four aspects of students' mathematical problem solving abilities, the average acquisition of aspects of understanding problems was 41.7% in the medium category, in the aspect of preparing a settlement plan 1.1% in the very low category, in the aspect of implementing the completion plan 69.4% in the high category. and in the aspect of re-examining, 45.4% was obtained in the medium category. The results of this study are expected to used as study material for other researchers in analyzing problem solving abilities in children.